2022
DOI: 10.1200/jco.2022.40.16_suppl.tps1118
|View full text |Cite
|
Sign up to set email alerts
|

KEYNOTE-B49: A phase 3, randomized, double-blind, placebo-controlled study of pembrolizumab plus chemotherapy in patients with HR+/HER2- locally recurrent inoperable or metastatic breast cancer.

Abstract: TPS1118 Background: HR+/HER2− advanced breast cancer that progresses on endocrine therapy is treated with chemotherapy (chemo). The phase 1b KEYNOTE-028 trial showed durable activity with pembrolizumab (pembro) monotherapy in previously treated HR+/HER2−, PD-L1–positive (combined positive score [CPS] ≥1) advanced breast cancer. KEYNOTE-B49 (NCT04895358) is a phase 3, randomized, double-blind study of pembro + chemo vs placebo (pbo) + chemo in centrally assessed PD-L1–positive, HR+/HER2− locally recurrent inop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“… 17 18 The role of PD-L1 expression in this population will be clarified by the ongoing phase III KEYNOTE-B49 trial assessing pembrolizumab in combination with chemotherapy in PD-L1-positive HR + mBC. 41 In our study, a numerical PFS benefit for the immune-chemo arm was observed for patients with a high Treg gene signature in tumor. This finding is of particular interest as preclinical studies have suggested that ipilimumab may deplete Tregs.…”
Section: Discussionsupporting
confidence: 50%
“… 17 18 The role of PD-L1 expression in this population will be clarified by the ongoing phase III KEYNOTE-B49 trial assessing pembrolizumab in combination with chemotherapy in PD-L1-positive HR + mBC. 41 In our study, a numerical PFS benefit for the immune-chemo arm was observed for patients with a high Treg gene signature in tumor. This finding is of particular interest as preclinical studies have suggested that ipilimumab may deplete Tregs.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, nivolumab plus eribulin showed ORR of 53.3% and median PFS of 5.6 months (95% CI, 4.3 to 6.8) in a phase IB/II study of HR+HER2– patients [ 79 ]. The currently ongoing KEYNOTE-B49 phase III trial is also evaluating the comparative efficacy of pembrolizumab in combination with one of four chemotherapy regimens, paclitaxel, nab-paclitaxel, doxorubicin, or capecitabine [ 80 ]. Additionally, a phase I/II trial of triple therapy with palbociclib, pembrolizumab, and letrozole in metastatic HR+/HER2– breast cancer observed 31% and 25% complete and partial response rates, inviting further research into the potential synergistic effects of immune checkpoint therapy with CDK4/6 inhibitors [ 81 ].…”
Section: Emerging Non-endocrine Therapies In Advanced Hr+ Breast Cancermentioning
confidence: 99%